Are active organic matter fractions suitable indices of management effects on soil carbon? A meta-analysis of data from the Pampas. Issue 11 (1st November 2016) - Alvarez, Carina Rosa; Alvarez, Roberto
ABSTRACT: Active fractions of organic matter have been proposed as early indices of changes in soil organic carbon (organic-C) induced by management. We performed a meta-analysis of published results from 31 field experiments conducted in the Pampas in which tillage and rotation effects on organic-C, microbial biomass carbon (microbial-C), light fraction carbon (light-C), particulate carbon (particulate-C) and basal respiration (mineralized-C) were assessed. We compared the changes of organic-C and the four active fractions between management treatments sampled at the same date and depth within each experiment. Pooling all the experiments, active fractions-C varied on average 1.2- to 3.0-fold more than organic-C, depending on the fraction considered, but these average changes were significantly greater than organic-C changes only for particulate-C. This later fraction showed to be more sensitive to agricultural practices than organic-C. In experiments in which organic-C changes were lower than 15–25%, the four labile fractions may show opposite trends than organic-C. Above this threshold, changes of active fractions generally copied organic-C changes and were greater. Consequently, the active fractions may be used as indicators of changes in organic-C only when this latter variable has already suffered a huge change. In these cases, it will be easier to simply measure organic-C.